1997
DOI: 10.1094/cchem.1997.74.5.621
|View full text |Cite
|
Sign up to set email alerts
|

Rye and Triticale as Feedstock for Fuel Ethanol Production

Abstract: Normal gravity rye and triticale mashes, containing 20–21 g of dissolved solids per 100 mL of mash liquid, were fermented with active dry yeast at 27°C. Fermentations were completed within 48 hr for rye, and within 72 hr for triticale. Supplementation of mashes with urea at a concentration of 8 mM accelerated rates of sugar consumption and fermentation, and reduced fermentation time from 48 to 36 hr for rye, and from 72 to 48 hr for triticale. Rye fermented faster than triticale, due to its higher level of fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Thus, the western Canadian ethanol industry generally utilizes wheat, which contributes about one-third to Canada's total ethanol production . Triticale, a cross between wheat and rye, also has potential for use as a substrate for bio-ethanol production as ethanol yield from triticale is similar to that from wheat (Wang et al 1997).…”
mentioning
confidence: 99%
“…Thus, the western Canadian ethanol industry generally utilizes wheat, which contributes about one-third to Canada's total ethanol production . Triticale, a cross between wheat and rye, also has potential for use as a substrate for bio-ethanol production as ethanol yield from triticale is similar to that from wheat (Wang et al 1997).…”
mentioning
confidence: 99%
“…There is limited information regarding the potential ethanol yields of small grain cereals in western Canada. Wang et al [1997] reported the spring triticale cultivar AC Copia yielded 362 to 367 L t -1 grain (14% moisture basis). Ethanol yields of 443 L t -1 of hulless barley (dry weight basis) have been reported .…”
Section: The Case For Wheat-based Bioethanolmentioning
confidence: 99%
“…A slightly narrower range was observed among the cultivars from 362 to 377 L t (1 . Wang et al (1997) reported the spring triticale cultivar AC Copia to yield 362Á367 L t (1 . There was a tendency among the cultivars that the cultivars with the higher ethanol yields in L t…”
Section: Triticalementioning
confidence: 99%
“…The efficiency of ethanol production from grains depends on process conditions, starch and fermentable sugar contents, and the presence and concentrations of pentosans in triticale and certain wheat classes (Wang et al 1997) or the b-glucans of barley and oat . These two components adversely affect process conditions through increases in mash and wort viscosities (Choct and Annison 1992).…”
mentioning
confidence: 99%